Titular roman catholic archbishop of Kuala Lumpur V Menteri Dalam Negeri & Anor: a legal analysis of article 10 and 11 of the federal constitution / Muhd Sajarul Erfhan Samsuddin … [et al.] - Samsuddin, Muhd Sajarul Erfhan; Mohd Inderam, Nurul Shahira; Ashari, Nur Aqilah; Muhammad Yusuf, Muhammad Syafiq (Faculty of Law, 2014)
This research study consists of five chapters on background, judicial principles in Titular case, and critical analysis on Article 10 and Article 11 of Federal Constitution. The purpose of this study is to analyses every law that enshrined the provisions and to provide a set of recommendation to resolve the issues arising from the usage of "Allah" word in the religious publication in Malaysia. This research will go further into analyzing the case involving the judicial decision in the case of Titular Roman Catholic Archbishop of Kuala Lumpur v Menteri Dalam Negeri & Anor (the Titular case). In addition, it is also to examine the impact of the decision against freedom of religion and expression Malaysia under Article 10 and 11 of Federal Constitution. This research is also essential as it highlights the importance of the revolution and reformation in shaping the actions of Malaysia government.